Desarrollo de un sistema de filtración utilizando materiales sinterizados como medios filtrantes (2016)
In the department of Boyacá there are rural areas which do not benefit from drinkable water, therefore the goal of the study is to create a filtering bed for water quality, with the aim of being used in these communities and reducing consumption and exposure to contaminants, in order to do so we used materials such as zeolite, bentonite, kaolonite and activated carbon which were submitted to a drying process at 110°C for six hours, afterwards they were used for the creation of four treatments of different proportions using as treatment one, 75% zeolite, 20% Bentonite,4.2% kaolonite and 0.8% activated carbon, for treatment two, 80% zeolite, 15% bentonite, 4.5% kaolonite and 0.5% activated carbon, for treatment three, 85% zeolite, 10% bentonite, 4.3% kaolin and 0.7% activated carbon and for treatment four, 85% zeolite, 10% bentonite, 4.6% kaolonite and 0.4% activated carbon. For the creation of this filtering bed capable of reducing contaminants we performed sifting procedures using meshes of 100, 270 and 400, applying a phase without a mill and another phase with a mill using the sifting method to obtain the filtering bed up to a temperature of 1000°C. These procedures were evaluated with the Porosity Analysis by SEM technique, the obtained results showed a decrease in the porosity of the sintered material, which were subjected to previously performed procedures. The analyses of the treatments were performed randomly; in the phase without a mill we obtained a pore size of 6, 23 and 3.56, microns for treatments 2 and 3, respectively, in the phase with a mill 2.390 microns for treatment 2.